دورِ جدید میں سیرت نگاری کے رجحانات - نوید احمدشہزاد (FIKR-O NAZAR فکر ونظر, 2009)
Being the living embodiment of the final version of the revealed guidance from the Creator for rest of the time Muhammad (peace be on him) is the role model for humanity in all affairs, till the day of judgment. This makes the knowledge of the life pattern (Sirah) of the Prophet (peace be on him) recurring need of the Muslim ummah. This recurring need of Sirah in seeking guidance for various aspects of individual and collective spheres of life made it inevitable for Muslim scholars to authentically record and then continually examine and re-examine the Sirah literature. This rigorous process of constant referral to Sirah for extracting guidance for a whole range of diverse affairs of life has motivated the scholars of Islam in each generation to recast Sirah literature in new idiom, adopting varying methodologies and styles over the span of last fourteen hundred years. The modern age gave rise to new issues as well as new means of textual and historical criticism. The scholars and specialists of Sirah un-reluctantly learned these tools of modern scholarship and have made serious efforts to utilise them in their endeavours of Sirah writing along with the traditional methods. This article attempts to study and introduce these fresh trends and methodologies which are being used by the scholars in producing Sirah literature in the modern times.